Engaged Egalitarianism: Why the Australian Recovery Must Prioritise Openness. Issue 2 (3rd June 2022) - Leigh, Andrew
Abstract : Australian living standards, relative to the rest of the world, have been highest in eras of economic openness. Openness can also increase equality. Tariffs tend to be regressive, so poor households benefit most from trade liberalisation. In the case of immigration, skilled permanent migrants tend to earn considerably more than the Australian‐born population, so any wage pressures are felt at the upper end of the distribution. Foreign investment can also have an equalising effect, by raising wages and lowering the rate of return on domestic capital. An approach of engaged egalitarianism – ensuring that the gains from globalisation are broadly shared – will benefit the most disadvantaged Australians.